Mechanism-oriented classification and structural control of rockburst based on a surrounding-rock structure field - Xukai Dong; Junwen Zhang; Xian Li; Jining Yang; Shaokang Wu (Geomatics, Natural Hazards & Risk)
Rockbursts in deep coal mining are triggered by complex structural instabilities within the surrounding rock mass. This study introduces the concept of the surrounding-rock structural field, which divides the coal-rock mass into three functional domains: the crushing-deformation domain, the damage-storage domain, and the fracture-disturbance domain. A mechanism-based classification system is developed, delineating five subtypes of rockburst-inducing instabilities according to the spatiotemporal sequence of failure events. Mathematical failure criteria for each domain are formulated through fracture mechanics and strength theory. Corresponding targeted control strategies – such as deep pre-split blasting and large-diameter borehole drilling – are proposed for each subtype. Field validations conducted across multiple mining sites demonstrate effective risk mitigation, evidenced by the spatial relocation of seismic events away from excavation areas. This research provides both theoretical insights and practical engineering guidance for precision prevention of rockbursts in deep mining operations.